2010
DOI: 10.1007/s00330-010-1869-5
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic contrast-enhanced CT in patients treated with sorafenib and erlotinib for non-small cell lung cancer: a new method of monitoring treatment?

Abstract: ObjectiveWe investigated the feasibility of serial dynamic contrast-enhanced computed tomography (DCE-CT) in patients with advanced/metastatic non-small cell lung cancer (NSCLC) receiving anti-angiogenic (sorafenib) and anti-EGFR (erlotinib) treatment, and correlated tumour blood flow (BF) with treatment outcome.MethodsDCE-CTs were performed at baseline and 3 and 6 weeks after starting treatment. Tumour BF, calculated with the maximum slope method, and percentage change were measured in 23 patients (14 male; m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(54 citation statements)
references
References 36 publications
2
51
0
1
Order By: Relevance
“…De Langen et al demonstrated that patients with lung cancer showed lower SUV max on 18 FDG PET-CT and decreasing tumour perfusion on DCE-MRI after anti-angiogenic therapy when compared to their baseline imaging [32]; similarly, Lind et al investigated the feasibility of DCE-CT in patients with advanced NSCLC who received anti-angiogenic and anti-EGFR treatment and found a significant decrease in tumour blood flow following targeted therapy. Moreover, early changes in tumour blood flow correlated with objective response and showed a trend towards longer progression free survival [33]. In another study involving 26 patients with stage III NSCLC, a significant decrease in the SUV max of the primary tumour was found a few weeks after the completion of preoperative chemoradiotherapy when compared with the baseline study.…”
Section: Discussionmentioning
confidence: 93%
“…De Langen et al demonstrated that patients with lung cancer showed lower SUV max on 18 FDG PET-CT and decreasing tumour perfusion on DCE-MRI after anti-angiogenic therapy when compared to their baseline imaging [32]; similarly, Lind et al investigated the feasibility of DCE-CT in patients with advanced NSCLC who received anti-angiogenic and anti-EGFR treatment and found a significant decrease in tumour blood flow following targeted therapy. Moreover, early changes in tumour blood flow correlated with objective response and showed a trend towards longer progression free survival [33]. In another study involving 26 patients with stage III NSCLC, a significant decrease in the SUV max of the primary tumour was found a few weeks after the completion of preoperative chemoradiotherapy when compared with the baseline study.…”
Section: Discussionmentioning
confidence: 93%
“…1) [10]. These trials date back to 1994 and have not only included drugs that target the tumour vasculature but also drugs with other therapeutic mechanisms (Table 3) [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56]. In some cases, the results from DCE-CT have assisted the "go-no go" decision concerning further drug development, and/or helped to determine a dose to take forward to later development phases.…”
Section: Dce-ct and Therapeutic Trials In Oncologymentioning
confidence: 99%
“…Although this technique confers a additional radiation dose to the patient, perfusion CT has many advantages such as being convenient and fast, and it has been used for the assessment of response to therapy of tumours in the head, liver, lung, pancreas, kidney, rectum, etc. [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 98%